2018
DOI: 10.1108/ijoa-08-2017-1206
|View full text |Cite
|
Sign up to set email alerts
|

Women’s enactment of leadership in a heavily gender-marked Islamic context

Abstract: Purpose Diverse cultural contexts with their distinct enactments of traditional gender inequity present unique constraints for female leaders. In Western contexts, the Christianity-inspired principle of equality of all humans remains a latent principle operative toward greater gender egalitarianism. This paper aims to examine female leaders within an Islamic context devoid of such espoused equality in which gender differences are enshrined in culture and law. Design/methodology/approach Questionnaires based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…All other papers focus on women in middle and senior positions in the companies. The authors of the main papers still focused their research on the USA and Europe, however, in other countries with higher indicators of inequality, especially developing ones, gender could play a bigger role, and thus, be a useful context to bring new insights to this discussion (Alhadhrami et al , 2018). The effects of culture in gender issues have to be considered when investigating these metaphors, and further research could, for instance, investigate the existence of these metaphors in overlooked countries, and thus, advance the understanding of the factors and consequences that these discriminatory practices bring to the lives of women.…”
Section: Discussionmentioning
confidence: 99%
“…All other papers focus on women in middle and senior positions in the companies. The authors of the main papers still focused their research on the USA and Europe, however, in other countries with higher indicators of inequality, especially developing ones, gender could play a bigger role, and thus, be a useful context to bring new insights to this discussion (Alhadhrami et al , 2018). The effects of culture in gender issues have to be considered when investigating these metaphors, and further research could, for instance, investigate the existence of these metaphors in overlooked countries, and thus, advance the understanding of the factors and consequences that these discriminatory practices bring to the lives of women.…”
Section: Discussionmentioning
confidence: 99%
“…The direction was extended further by Pradhan and Jena (2017); they confirmed that abusive supervision is strongly related to subordinates’ intention to quit. Further studies cleared the doubts; there is no difference in women leadership and male leadership, except in brokering skills in which women are perceived as superior to male counterparts, so their leadership has an equivalent impact in the organization (Alhadhrami et al , 2018). The organizational culture plays a vital role in influencing the leader’s style and the effect of the chosen leadership style on the team’s performance (Maamari and Saheb, 2018).…”
Section: Thematic Cluster Analysis and Future Directionsmentioning
confidence: 99%
“…Diverse cultural contexts with distinctive elements of gender inequality exhibit unique constraints for women leadership and inclusion in the workplace (Alhadhrami et al , 2018). The Japanese corporate world has often been described as built on strongly gendered practices (Adler, 1994; Benson and Yukongdi, 2005; Liddle and Nakajima, 2004; Saito, 2017; Sugihara and Katsurada, 2002).…”
Section: Introductionmentioning
confidence: 99%